Grace and the Bully 1819 - Lutz, Norma Jean; Nang Chan Yeema (Uhrichsville, OH USA Barbour Publishing, Inc., 2006)
As Grace and her cousin's family finances dry up like the once mighty river, they learn an important lesson about judging others.
Keywords: Adult Fiction